Assessment of pesticides removal using two-stage Integrated Aerobic Treatment Plant (IATP) by Bacillus sp. isolated from agricultural field - Geed S.R.; Shrirame B.S.; Singh R.S.; Rai B.N. (My University, 2025)
The biodegradation of synthetic wastewater containing Atrazine, Malathion and Parathion was studied in two stage Integrated Aerobic Treatment Plant using Bacillus sp. (consortia) isolated from agricultural field. The influent stream containing these pesticides with initial COD of 1232 mg/L were fed to first reactor and treated effluent of first reactor was fed to second reactor. The maximum removal of pesticides in IATP was found to be greater than 90%. The various process parameters such as pH, DO, Redox potential and BOD5/COD were monitored during the treatment. The degradation of pesticides and its metabolites in the treated effluent were confirmed by GC–MS. Kinetic parameters such as first order rate constant (Kobs), cell yield (YX/C) and decay coefficients (Kdp) were evaluated and found to be 0.00425 per hr, 0.696 mg of COD/mg MLSS and 0.0010 per hr respectively. This integrated process was found more effective than physico-chemical treatment of pesticides. © 2017 Elsevier Ltd